The impact of environmental, social and governance practices (ESG) on firms’ performance and value in the euro area member states clustered by debt-to-GDP ratio in the period 2010 – 2022 - Valerianová, Lenka (2024)
This thesis explores whether the effect of ESG score on firm performance and value differs between two groups of euro area member countries, differentiated by debt-to-GDP ratio relative to the EU average for the period 2010-2022. Empirical evidence of differences between the two groups is indeed found. The coefficients of ESG scores tend to be lower in value in the group of more indebted countries than in the group of the less indebted ones. Particularly when firm performance is used as dependent variable, the impact of environmental pillar is strongly significant and positive for the less indebted countries, while for the more indebted ones, it is negatively insignificant. For the same dependent variable, the governance pillar is positively insignificant for the less indebted countries, while for the more indebted ones, it is weakly significant and negative. These results imply that high government indebtedness could be detrimental to the effect of ESG on firms' performance, which in turn might lead to a decrease in local incentives to invest in sustainable development.